Health psychology theory, research and practice - Marks, David (David F.); Murray, M. 1952-; Estacio, Emee Vida (SAGE, 2018)
"The fifth edition of this essential text further advances a critical perspective on health while introducing readers to emerging issues such as long-term conditions and end-of-life care."--Cover, p.[4]